How Busyness Influences SEC Compliance Activities: Evidence from the Filing Review Process and Comment Letters - Gunny, Katherine A.; Hermis, Judith M. (Contemporary Accounting Research, 2020)
ABSTRACT The SEC reviews firm filings and issues comment letters on those filings. These comment letters play an important role in the assessment of firm value. These activities are seasonally compressed because over 70 percent of registrants have a December fiscal year‐end. Research in other settings finds that busyness leads to negative outcomes. We examine how busyness impacts the frequency, scope, and timeliness of comment letters. We find that the SEC issues fewer comment letters when busy, focuses its limited resources on the most severe cases of disclosure noncompliance, and extends the amount of time between receiving a firm's filing and issuing a comment letter. Despite this, we find no evidence that the SEC misses more serious compliance issues when busy. Our results have implications for policymakers responsible for allocating resources to the SEC.